2021
DOI: 10.3324/haematol.2021.278603
|View full text |Cite
|
Sign up to set email alerts
|

RXRA DT448/9PP generates a dominant active variant capable of inducing maturation in acute myeloid leukemia cells

Abstract: The retinoid receptors RARA and RXRA contribute to myeloid maturation in both mice and humans, and deletion of Rxra and Rxrb augments leukemic growth in mice. While defining the domains of RXRA that are required for anti-leukemic effects in mouse KMT2A-MLLT3 leukemia cells, we unexpectedly identified RXRA DT448/9PP as a constitutively active variant capable of inducing maturation and loss of their proliferative phenotype. RXRA DT448/9PP was associated with ligand-independent activity in reporter assays, with e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“… Di Martino et al (2021a) showed that deleting endogenous RXRA in an MLL-AF9 AML mouse model increased leukemogenic potential and reduced survival. The same authors subsequently reported that a constitutively overexpressing mutant variant of RXRA resulted in myeloid maturation and prolonged survival in the murine model ( Di Martino et al, 2021a ; Di Martino et al, 2021b ). In line with this, in our RXRA overexpressing CDX CML mice model, we observed decreased leukemic burden and improved survival compared to EV-transduced CDX.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“… Di Martino et al (2021a) showed that deleting endogenous RXRA in an MLL-AF9 AML mouse model increased leukemogenic potential and reduced survival. The same authors subsequently reported that a constitutively overexpressing mutant variant of RXRA resulted in myeloid maturation and prolonged survival in the murine model ( Di Martino et al, 2021a ; Di Martino et al, 2021b ). In line with this, in our RXRA overexpressing CDX CML mice model, we observed decreased leukemic burden and improved survival compared to EV-transduced CDX.…”
Section: Discussionmentioning
confidence: 94%
“…The dual activation of RXRA-RARA heterodimers by the specific ligands, ATRA and bexarotene effectively targeted MLL-AF9 myelomonocytic leukemic cells in-vitro and improved the survival in-vivo in mice models ( Di Martino et al, 2021a ). DT448/9PP mutated RXRA receptor overexpression enhanced transcriptional activity leading to differentiation and loss of colony-forming ability in KMT2A-MLLT3 transformed AML cells ( Di Martino et al, 2021b ). Bexarotene treatment increased the protein expression of RXR isoforms ( RXRA , RXRB & RXRG ) in SH-SY5Y cells ( Dheer et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Direct binding of MLLT3 to Retinoic Acid Receptors recruits the super elongation complex to rapidly induce neural programmes ( 80 ). Moreover, a mutant form of RXRα disrupts proliferation in murine KMT2A-MLLT3 leukemia cells ( 92 ). Consistent with a relationship between MLLT3 and RA signalling, our results from complementary approaches, indicate that disrupting the ability of RARα to interact with MLLT3 phenocopied the neural tube defects observed with perturbing MLLT3 .…”
Section: Discussionmentioning
confidence: 99%
“…Luciferase detection. HEK293T cells were transfected using Lipofectamine 2000 (Invitrogen) [80]. Six hours after transfection, the cells were collected and plated into a 48-well plate in 1% BSA media in biological triplicates and treated with compounds.…”
Section: Methodsmentioning
confidence: 99%